2018
DOI: 10.1007/s10856-018-6190-x
|View full text |Cite
|
Sign up to set email alerts
|

Bio-inspired melanin nanoparticles induce cancer cell death by iron adsorption

Abstract: Dysregulation of iron metabolism is a common characteristic of cancer cells. The rapid proliferation of the tumour cells means that there is an increased dependence upon iron compared to healthy cells. Chelation of iron can be undertaken with a number of different compounds, however, simply lowering systemic iron levels to control tumour growth is not possible since iron is essential for cellular metabolism in the rest of the body. Nanoparticulate iron chelators could overcome this difficulty by targeting to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…These suggest that a low glucose diet (e.g., ketogenic) for cancer therapies based on nanoparticles could be beneficial. Our results are in broad agreement with other reports on a variety of cancer cells [ 47 , 48 , 49 , 50 ].…”
Section: Resultssupporting
confidence: 94%
“…These suggest that a low glucose diet (e.g., ketogenic) for cancer therapies based on nanoparticles could be beneficial. Our results are in broad agreement with other reports on a variety of cancer cells [ 47 , 48 , 49 , 50 ].…”
Section: Resultssupporting
confidence: 94%
“…Given that redox and non-redox metal ions can lead to the production of ROS and are involved in the pathology of neurological diseases, the removal of excess metal ions is a sensible therapeutic in oxidative stress-involved neurological diseases. Melanin NPs can chelate iron to impede the Fenton reaction and block the generation of ·OH in ischemic brains [ 5 , 144 ]. In addition, polymer- or inorganic-NPs-based nanocarriers loaded with natural prototype metal chelators have been tried for chelation therapy in neurological diseases.…”
Section: Inhibiting Rons Generation Rather Than Scavenging Ronsmentioning
confidence: 99%
“…PDA also behaves as an antineoplastic system, selectively killing tumor cells without causing toxicity to healthy cells [ 97 , 137 ]. Perring et al showed that water-soluble melanin NPs induced selective cytotoxicity in human rhabdomyosarcoma (RH30, and RD) and glioblastoma (U-87 MG and Mo59K) tumor cell lines via iron deprivation, which is due to the chelating properties of melanin polymers [ 138 ]. In another study, Gabriele et al reported that highly monodispersed uncoated and glucose-coated MEL-NPs are massively absorbed by malignant cancer cells and influence their viability, which reduces with increasing numbers of absorbed NPs [ 139 ].…”
Section: Melanin-based Targeted Cancer Therapymentioning
confidence: 99%